PENGARUH MOTIVASI, DISIPLIN KERJA DAN PRESTASI KERJA TERHADAP PRODUKTIVITAS KERJA (Studi kasus pada bagian produksi PT. Kimia farma (persero) Tbk Plan Semarang) - Muchammad Taufan; Handoyo Djoko Waluyo; Reni Shinta Dewi (Universitas Diponegoro, 2013)
Productivity is a measure that is often used to determine the effectiveness of the organization. An organization can not flourish if their employees work productivity also increased especially with the high level of competition that exists in the business world. Motivation, discipline and work performance have been found to increase employee productivity. Therefore these three things need to be considered by the management company in order to increase employee productivity. PT. Kimia Farma (Persero) Tbk Plant Semarang is one of the state-owned company that manufactures drugs. This study uses an associative approach to the 62 respondents with sampling purposive sampling technique. Data collection techniques in this study were interviews, questionnaires and literature study. The data obtained were analyzed qualitatively and quantitatively by using tools such as cross-table analysis, validity, reliability testing, simple linear regression, multiple linear regression and hypothesis testing with the t test and F test with SPSS 17. These results indicate a positive significant effect between motivation toward work productivity of employees of PT. Kimia Farma (Persero) Tbk Plant Semarang where t (14.701)> t table (1.670), a significant difference between the positive work discipline to employee productivity PT. Kimia Farma (Persero) Tbk Plant Semarang where t (15.585)> t table (1.670) and a significant difference between the positive achievements of the labor productivity of employees of PT. Kimia Farma (Persero) Tbk Plant Semarang where t (17.007)> t table (1.670). There is a significant positive influence between work motivation, work discipline and work performance of the employee productivity PT. Kimia Farma (Persero) Tbk Plant Semarang where F count (149.641)> F table (2,76). The coefficient of determination for the work motivation variables (X1), labor discipline (X2) and work performance (X3) accounted for 88% of employee productivity PT. Kimia Farma (Persero) Tbk Plant Semarang, while 12% are influenced by other factors. Suggestions can be submitted is a portion of the company must give priority to larger or better application of motivation in the company, due to the influence of motivation on employee performance is lower than the effect of labor discipline and job performance on employee productivity.